Notification of crop varieties and registration of germplasm : Durum wheat, Variety UAS 446 - Desai, S.A. (The Indian Journal of Genetics and Plant Breeding, 2016)
Wheat is one of the major rabi crop in the Peninsular zone of Indian wheat belt comprising Maharashtra and Karnataka states. Majority of the wheat crop is grown under rainfed condition in this zone and durum wheats have remarkable share in total wheat production in the zone. Â Under such conditions, crop is exposed to early and terminal heat stress conditions as major abiotic factors. The brown and black rusts are also crucial biotic stresses that affect wheat yields.